Industry Compensation under Relocation Risk: A Firm-Level Analysis of the EU Emissions Trading Scheme - Martin, Ralf; Muûls, Mirabelle; de Preux, Laure B.; Wagner, Ulrich J. (The American economic review, 2014)
When regulated firms are offered compensation to prevent them from relocating, efficiency requires that payments be distributed across firms so as to equalize marginal relocation probabilities, weighted by the damage caused by relocation. We formalize this fundamental economic logic and apply it to analyzing compensation rules proposed under the EU Emissions Trading Scheme, where emission permits are allocated free of charge to carbon-intensive and trade-exposed industries. We show that this practice results in substantial overcompensation for given carbon leakage risk. Efficient permit allocation reduces the aggregate risk of job loss by more than half without increasing aggregate compensation.